2022
DOI: 10.3390/ijerph192315872
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Adolescents’ Participation in Organized Sports

Abstract: Participation in organized sports has important health benefits in adolescence, yet participation rates are concerning. A better understanding of factors influencing adolescents’ participation in organized sports offers opportunities to improve participation rates. The aim of this study was to examine to what extent motives, perceived competence, encouragement and motor skills were associated with participation in organized sports in a sample of first-year secondary school students. In this cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In this regard, Lamoneda and Huertas-Delgado [7] indicated that, of the BPNs, perceived competence was also the most positively predictive of PA. A similar study [1], on school soccer, reported that the more competent students feel, the greater their adherence to this sport. In a study with adolescents [51], perceived competence was also significantly associated with their participation in organized sports. Therefore, interventions based on SDT [2], supported by BPNs, could be a useful didactic strategy to motivate primary students to practice PA in other contexts.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, Lamoneda and Huertas-Delgado [7] indicated that, of the BPNs, perceived competence was also the most positively predictive of PA. A similar study [1], on school soccer, reported that the more competent students feel, the greater their adherence to this sport. In a study with adolescents [51], perceived competence was also significantly associated with their participation in organized sports. Therefore, interventions based on SDT [2], supported by BPNs, could be a useful didactic strategy to motivate primary students to practice PA in other contexts.…”
Section: Discussionmentioning
confidence: 97%
“…However, in order to realize the full potential of youth sports and specifically the sports club, to be a positive place for development, it is crucial to align and secure the activities of, among others, coaches, other guides (e.g., parents) and policymakers towards a positive and safe sports climate always taking into account the motives and barriers of youngsters that are under their responsibility [29,30]. The findings of this study provide directions for the development of future interventions that improve sports participation and prevent dropout from sports [14,16]. It supports sports organizations and coaches to create an optimal environment for youth in sports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified several factors that influence sport participation within this target group, including, among others, enjoyment, perceived competence and social support [12,13]. Yet, a recent study within the Dutch context showed that especially adolescent motives are key determinants regarding sport participation [14]. This study examined a combination of factors based on the Youth Physical Activity Promotion model [15] (i.e., motives, perceived competence, encouragement and motor skills) to better understand factors influencing adolescents' sport participation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A previous study, on school soccer [1], reported that the more competent students feel, the greater their adherence to this sport. In a study with adolescents [45], perceived competence was significantly associated with their participation in organized sports. Therefore, interventions based on Self-Determination Theory, supported by BPNs, could be a useful didactic strategy to motivate primary students to practice physical activity in other contexts.…”
Section: Bpnsmentioning
confidence: 97%